Ferromagnetism and Half‐Metallicity in a High‐Band‐Gap Hexagonal Boron Nitride System - Choudhuri, Indrani; Pathak, Biswarup (Chemphyschem, 2018)
Metal‐free half‐metallicity is the subject of intense research in the field of spintronics devices. Using density functional theoretical calculations, atom‐thin hexagonal boron nitride (h‐BN)‐based systems are studied for possible spintronics applications. Ferromagnetism is observed in patterned C‐doped h‐BN systems. Interestingly, such a patterned C‐doped h‐BN exhibits half‐metallicity with a Curie temperature of approximately 324 K at a particular C‐doping concentration. It shows half‐metallicity more than metal‐free systems studied to date. Thus, such a BN‐based system can be used to achieve a 100 % spin‐polarised current at the Fermi level. Furthermore, this C‐doped system shows excellent dynamical, thermal, and mechanical properties. Therefore, a stable metal‐free planar ferromagnetic half‐metallic h‐BN‐based system is proposed for use in room‐temperature spintronics devices. Spin doctored: DFT calculations are performed on carbon‐doped hexagonal boron nitrides (h‐BN). These materials exhibit ferromagnetism, half‐metallicity, and favorable dynamical, thermal, and mechanical properties. Patterned C‐doped h‐BNs are therefore promising materials for spintronics applications.